The Impact of Pelvicalyceal System Anatomy on Stone Formation in Patients with Single Lower Pole Calyceal Stone on Computed Tomography Urography - Adhikari, Kapil; Regmi, Niraj; Devkota, Karun; Koirala, Sapana (Journal of Nepal Health Research Council, 2024)
Background: To compare various lower pole pelvicalyceal anatomical factors of stone bearing kidney with contralateral normal kidneys and determine whether these factors predispose to stone formation in one kidney. Methods: A descriptive study was done with Computed Tomography of 54 patients with solitary lower pole calculus in one kidney and normal contralateral kidney were included. Various lower pole pelvicalyceal anatomical factors like infundibulopelvic angle, infundibular width, infundibular length and calyceopelvic height of both stone bearing and contralateral kidneys were measured and compared for any differencesResults: The mean infundibular width was 5.4±1.9mm on stone bearing kidneys and 5.2±2.05mm on contralateral normal kidneys. The mean infundibular length was 18.9±4.4mm on stone bearing kidneys and 18.8±3.9mm on contralateral normal kidneys. The mean infundibulopelvic angle was 47.9±10.8° on stone bearing kidneys and 47.6±11.2° on contralateral kidneys. The mean calyceopelvic height was 15.7±4.6mm on stone bearing kidneys and 15.5±3.9mm (range 7.5to 23.1mm) on contralateral kidneys. There were no statistically significant differences between stone bearing and contralateral normal kidneys in respect to these pelvicalyceal anatomical factors.Conclusions: In this study, we found no significant difference in lower pole pelvicalyceal anatomical factors between stone bearing kidneys and contralateral normal kidneys and therefore these factors do not seem to have significant role in stone formation in one kidney compared with the other.Keywords: Lower pole calculus; pelvicalyceal anatomical factors; urography.